Media audit reveals inappropriate promotion of products under the scope of the International Code of Marketing of Breast-milk Substitutes in South-East Asia. Issue 8 (15th March 2017) - Vinje, Kristine Hansen; Phan, Linh Thi Hong; Nguyen, Tuan Thanh; Henjum, Sigrun; Ribe, Lovise Omoijuanfo; Mathisen, Roger
Abstract: Objective: To review regulations and to perform a media audit of promotion of products under the scope of the International Code of Marketing of Breast-milk Substitutes ('the Code') in South-East Asia. Design: We reviewed national regulations relating to the Code and 800 clips of editorial content, 387 advertisements and 217 Facebook posts from January 2015 to January 2016. We explored the ecological association between regulations and market size, and between the number of advertisements and market size and growth of milk formula. Setting: Cambodia, Indonesia, Myanmar, Thailand and Vietnam. Results: Regulations on the child's age for inappropriate marketing of products are all below the Code's updated recommendation of 36 months (i.e. 12 months in Thailand and Indonesia; 24 months in the other three countries) and are voluntary in Thailand. Although the advertisements complied with the national regulations on the age limit, they had content (e.g. stages of milk formula; messages about the benefit; pictures of a child) that confused audiences. Market size and growth of milk formula were positively associated with the number of newborns and the number of advertisements, and were not affected by the current level of implementation of breast-milk substitute laws and regulations. Conclusions: The present media audit reveals inappropriate promotion and insufficient national regulation of products under the scope of the Code in South-East Asia. Strengthened implementation of regulations aligned with the Code's updated recommendation should be part of comprehensive strategies to minimize the harmful effects of advertisements of breast-milk substitutes on maternal and child nutrition and health.